1992
DOI: 10.1080/01904169209364488
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene evolution and ammonium accumulation by tomato plants under water and salinity stresses. Part II

Abstract: Foliar wilting, epinasty, abscission, chlorosis, and necrosis are common symptoms in plants affected by water and salinity stresses. Ethylene evolution and ammonium accumulation frequently accompany the expression of the symptoms of stresses from various origins. These symptoms and physiological phenomena have been associated with other environmental stresses, such as ammonium toxicity. Intact and excised tomato plants (Lycopersicon esculentum Mill. 'Heinz 1350' and neglecta-1) were subjected to stresses of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…In the present study we found an increase in salt concentration gradually enhanced ethylene production in red pepper seedlings, which is in agreement with earlier studies (Bar and others 1998; Feng and Barker 1992;Lutts and others 1996;Mayak and others 2004). Ethylene sensitivity differs from species to species and cultivar to cultivar (Zapata and others 2007) and even depends on environmental conditions such as light (Mortensen 1989), O 3 , CO 2 , and so on (Morgan and Drew 1997).…”
Section: Discussionsupporting
confidence: 95%
“…In the present study we found an increase in salt concentration gradually enhanced ethylene production in red pepper seedlings, which is in agreement with earlier studies (Bar and others 1998; Feng and Barker 1992;Lutts and others 1996;Mayak and others 2004). Ethylene sensitivity differs from species to species and cultivar to cultivar (Zapata and others 2007) and even depends on environmental conditions such as light (Mortensen 1989), O 3 , CO 2 , and so on (Morgan and Drew 1997).…”
Section: Discussionsupporting
confidence: 95%
“…In Arabidopsis seedlings, subjected to two levels of salinity, ethylene production increased, in proportion to the concentration of NaCl applied (Hall and Smith 1995). Accordingly, in tomato and cucumber, increasing salt concentration in the rooting zone gradually increased leaf ethylene production rates, which appeared to promote leaf senescence (Feng and Barker 1992;Helmy et al 1994), while in Carrizo citrange, increased ethylene production induced leaf abscission (Gómez-Cadenas et al 1998, 2003Arbona et al 2003a). NaCl treatment has also been shown to increase ethylene synthesis in leaves of a number of rice cultivars, which was linked to the salt-sensitivity of the cultivars (Lutts et al 1996).…”
Section: Introductionmentioning
confidence: 94%
“…They found a more significant increase in proline, induced by salinity, when plants had been exposed to NO 3 -plus NH 4 + than when they had been fed with NO 3 -alone. Feng and Barker [9] showed that application of NH 4 + to tomato plants under saline stress increased toxic symptoms expressed as chlorosis and necrosis. However, little is known about the effect of N-form combined with saline water, in the nutrient solution, on fruit quality.…”
Section: Introductionmentioning
confidence: 99%